A comparison of perceptions of the tuberculin skin test and an incentive postmortem-based surveillance system in the Mnisi community, Mpumalanga, South Africa - Morar-Leather, Darshana (University of Pretoria, 2025)
Dissertation (MSc (Tropical Animal Health))--University of Pretoria, 2018.